Effect of tilt angle and connection mode of PVT modules on the energy efficiency of a hot water system for high-rise residential buildings. (August 2016) - Sun, L.L.; Li, M.; Yuan, Y.P.; Cao, X.L.; Lei, B.; Yu, N.Y.
Abstract: The tilt angle and connection mode of PVT modules are critical factors influencing the energy efficiency of PVT systems. To evaluate their effect, we built a PVT hot water system which is naturally driven by gravity and the PVT modules are installed on vertical facades of high-rise residential buildings. We develop a dynamic model for the simulation of the PVT hot water system. The simulation results are in good agreement with indoor experimental data. Compared with parallel connection, electric power for series connection decreases by 2.0%, thermal energy increases by 11.4% and total energy increases by 5.4%. The connection mode has more obvious influences on thermal energy than electrical power. Considering only total energy, PVT modules with a tilt angle of 20° can produce maximum energy benefits. However, the projection lengths of PVT modules should also be considered when selecting the optimum tilt angle. The optimum tilt angle is chosen as 40° when both total energy and projection length are considered. These findings are good references for the installation of PVT modules on vertical facades of high-rise residential buildings. Highlights: A PVT hot water system using vertical facades is proposed for high-rise buildings. The PVT hot water system is driven by natural circulation. The dynamic simulation model of the PVT hot water system is developed and validated. The effects of tilt angle and connection mode of PVT modules are investigated. The series connection can increase the total energy benefits by about 5.4%.